2018
DOI: 10.3390/agriculture8010016
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Knowledge on Pesticide Safety and Pest Management Practices: A Case Study of Vegetable Growers in Chitwan, Nepal

Abstract: Farmers' knowledge on pesticides and their safe use are critical for implementing effective pest management program. A household survey was conducted using the semi-structured questionnaire to evaluate vegetable growers' knowledge on pesticide safety and pest management practices in Nepal. Results indicated that chemical pesticides were the primary choice of over 80% growers for pest management. Notably, 90% growers were aware of adverse effects of pesticides on human health and to the environment. Over 84% gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 24 publications
7
64
1
2
Order By: Relevance
“…A similar result was observed in Chitwan district. Around 58% of Chitwan's farmers had sprayed pesticides >4 times/season whereas 38% farmers applied pesticides 1-3 times/season (Rijal et al, 2018). The study conducted by Khanal and Singh (2016) also showed an increasing trend of unrestricted use of pesticides by vegetable farmers in Chitwan district.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A similar result was observed in Chitwan district. Around 58% of Chitwan's farmers had sprayed pesticides >4 times/season whereas 38% farmers applied pesticides 1-3 times/season (Rijal et al, 2018). The study conducted by Khanal and Singh (2016) also showed an increasing trend of unrestricted use of pesticides by vegetable farmers in Chitwan district.…”
mentioning
confidence: 90%
“…Nearly 11% of the farmers sprayed pesticides after pests damage their crops. A study conducted by Rijal et al (2018) in Chitwan district reported that about 54% of the farmers sprayed pesticides right after the appearance of pests. Two-fifths of the potato growers did not account for windy days for pesticide spraying.…”
mentioning
confidence: 99%
“…Tarla et al and Sonchieu et al [4]- [9] have reported similar information in the same areas but in different villages. This common knowledge will obviously lead to the least variation of amount of pesticide residues in various foods produced in the very area [14]. The high number of years of experience can be an indicator of either high or low exposure of the consumer because the spraying factors could have been the same during that long period in cropping activity.…”
Section: Discussionmentioning
confidence: 99%
“…mask only, mask and boot only). Rijal et al (2018) reported that 34% of farmers use masks only and 14% of farmers do not use PPE at all while spraying the pesticide. About 26.3% of the respondents safely maintain their equipment and 39.8% of respondent keep the record of the use of pesticides.…”
Section: Crop Protectionmentioning
confidence: 99%